Student Obedience and Spiritual Well-Being in Islamic Education: Exploring the Role of Adab in Teacher–Student Relationships - Dwi Cinta Nur Sabila; Desylia Widyasari; Ismail Ismail; Zainudin Hasan (Journal of Islamic Education Thought and Development, 2026)
This study investigates the relationship between student obedience to teachers and students’ inner satisfaction within the context of Islamic boarding school education. Despite extensive discussions on teacher–student relationships in Islamic education, limited research has explored how obedience grounded in adab (ethical conduct) contributes to students’ spiritual well-being and learning experiences. Employing a qualitative case study design, this research involved eight students selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and document analysis and were analyzed using the Miles and Huberman interactive model. The findings reveal three major themes. First, obedience rooted in adab is associated with psychological tranquility, enhanced knowledge internalization, and the emergence of hudhur al-qalb (presence of heart), which students perceive as a form of inner satisfaction during the learning process. Second, students’ compliance is shaped by multiple factors, including teachers’ role modeling, students’ understanding of the philosophical foundations of institutional rules, and the influence of the surrounding social environment. These factors significantly affect students’ emotional stability and attitudes toward learning. Third, sustainable obedience is more effectively fostered through value internalization, reflective guidance, and open dialogue than through fear-based disciplinary approaches. This study contributes to the literature on Islamic education by conceptualizing obedience not merely as behavioral conformity but as a multidimensional process linked to spiritual well-being and meaningful learning. The findings suggest that educational institutions can strengthen students’ holistic development by promoting adab-based educational practices that integrate moral formation, supportive teacher–student relationships, and reflective engagement with institutional norms.